2020
DOI: 10.1136/bmjgh-2019-001875
|View full text |Cite
|
Sign up to set email alerts
|

The global and regional burden of genital ulcer disease due to herpes simplex virus: a natural history modelling study

Abstract: IntroductionHerpes simplex virus (HSV) infection can cause painful, recurrent genital ulcer disease (GUD), which can have a substantial impact on sexual and reproductive health. HSV-related GUD is most often due to HSV type 2 (HSV-2), but may also be due to genital HSV type 1 (HSV-1), which has less frequent recurrent episodes than HSV-2. The global burden of GUD has never been quantified. Here we present the first global and regional estimates of GUD due to HSV-1 and HSV-2 among women and men aged 15–49 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 103 publications
2
59
0
Order By: Relevance
“…Another finding of this study is that HSV-2 infection is the cause of half of GUD cases in SSA (Table 5), confirming that this infection is the main cause of this disease in this part of the world where nearly 60 million individuals are estimated to be affected with HSV-related GUD. (79)…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of this study is that HSV-2 infection is the cause of half of GUD cases in SSA (Table 5), confirming that this infection is the main cause of this disease in this part of the world where nearly 60 million individuals are estimated to be affected with HSV-related GUD. (79)…”
Section: Discussionmentioning
confidence: 99%
“…However, DRG infection was rare, suggesting potent protection when using DRG as a marker for vaccine efficacy. Fourth, HSV-1 comprises only 5% of the global burden of genital herpes [3]. HSV-1 genital infections reactivate at a lower frequency than HSV-2 [5].…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus type 2 (HSV-2) genital infection affects a half-billion people worldwide [1]. Herpes simplex virus type 1 (HSV-1) genital infection affects an additional 190 million people [2,3]. Fifty percent of first-time genital herpes infections in resource-rich countries are caused by HSV-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genital herpes is predominantly attributed to HSV-2 infection, while HSV-1 primarily infects the oral cavity, but can also affect the genital tract. 1 Several studies have reported an increasing prevalence of genital HSV-1 infection. 2 3 Genital inflammation is associated with increased risk of HIV infection in young women.…”
Section: Introductionmentioning
confidence: 99%